A systematic literature review of the latest instructional models for teaching English writing - Herdi Herdi; Ribut Wahyu Eriyanti; Diah Karmiyati; Marwa Marwa; Fauzan Fauzan (Perspectives in Education)
Considering the universality of writing struggles faced by both the students and teachers, it is an unexpected observation to find that there are most likely only a dozen or so systematic reviews on the topic. Among these reviews, none so far have focused on identifying and discussing English writing instructional models. This paper systematically reviewed original research papers on English writing instructional models that were published from 2020 to 2024. Using tools such as Publish and Perish, R Studio and NVivo to review the eligible 86 studies, this study identified 60 instructional models for teaching English writing, 25 of them having been newly developed and proposed in the last five years. The names of every instruction or teaching models that were identified are organized based on ten commonalities that several models share: template-based (6), genre-specific (6), discussion-based (8), ICT-based (10), feedback-based (3), focused on lesson plan (10), integration (5), insight (3), collaboration (6), and country-specific (3). A novelty of this systematic review is that it focused on discussing the writing instructional models and presented them by themes that make them easily comparable and easy-to-use for teachers who are aiming to change and improve the way they teach English writing.